IJCM_80A: A Study on Risk factors and outcome of post partum hemorrhage among postnatal mothers attending a tertiary care hospital in Guntur District - Sankeerti M.; Rajesh A. Hani; Rama A. Sita (Wolters Kluwer Medknow Publications, 2024)
Background: Post Partum Haemorrhage (PPH) is a major cause of maternal mortality and morbidity worldwide. PPH is the most common form of major obstetric haemorrhage. Majority of deaths due to PPH are reported to be in developing countries and the major factors responsible were attributed to lack of access to reproductive health services, availability of skilled health personnel, timely intervention of obstetric emergencies and others such as appropriate equipment and supplies. With increase in rate of institutional deliveries and improvement in quality of services MMR can further be reduced with focus on the factors responsible for maternal deaths. Objective: The study was aimed to identify risk factors of postpartum hemorrhage among postnatal mothers and to analyze various factors and determinants that influence the outcome among mothers with PPH. Methodology: This was a descriptive observational retrospective study conducted in Department of obstetrics and Gynecology, government general hospital, Guntur. The target population included 50 postnatal mothers diagnosed as having PPH. Other causes of hemorrhage not related to delivery such as accidents and women with preexisting medical and other conditions were excluded. Data was collected from the available medical records Results: The prevalence of PPH was 0.96%. The causative factors identified were atonic uterus (80%), traumatic delivery (17.5%) and retained bits (1.7%). Induced labor (16%), prolonged labor (11.1%) and preeclampsia (3.4%) were the risk factors that lead to PPH. The mortality was 4% (2) and the cause of death in the 2 patients was due to shock. Conclusion: In the present study, the prevalence of postpartum hemorrhage (PPH) was recorded at 0.96%. Uterine atony emerged as the primary contributing factor, with induced labor identified as the leading risk factor associated with an increased predisposition to PPH. Shock stood out as the predominant cause of mortality.